(a-4)²-2a(3a-4)=0 Раскрываем скобки, 1-с формулы (а-b)²=a²+2ab+b², вторую скобку-перемножая. (a-4)²=a²-2*4*a+4²=a²-8a+16 2a(3a-4)=2a*3a-2a*4=6a²-8a a²-8a+16-(6a²-8a)=a²-8a+16-6a²+8a=-5a²+16(т.к. 8а сократятся) Если а=-1, тогда -5*(-1)²+16=-5+16=11 Если что, (-1)²=1
Раскрываем скобки, 1-с формулы (а-b)²=a²+2ab+b², вторую скобку-перемножая.
(a-4)²=a²-2*4*a+4²=a²-8a+16
2a(3a-4)=2a*3a-2a*4=6a²-8a
a²-8a+16-(6a²-8a)=a²-8a+16-6a²+8a=-5a²+16(т.к. 8а сократятся)
Если а=-1, тогда -5*(-1)²+16=-5+16=11
Если что, (-1)²=1